Status of Interoperability Requirements related to IHE Integration Profiles in Finland - Hannu Virkanen; Juha Mykkänen; Terhi Kajaste (Finnish Social and Health Informatics Association, 2010)
IHE (Integrating the Healthcare Enterprise) integration profiles provide means for uniform application of central interoperability standards for specific use cases in healthcare. The IHE model involves global development and local deployment of integration profiles. This paper reports the results of a national survey and a set of expert interviews which explored the current integration needs of healthcare organizations, application vendors and national health IT initiatives in relation to the requirements covered by IHE integration profiles. For several integration needs, the use cases of IHE integration profiles match the current needs of the respondents. IT infrastructure and radiology profiles received most responses, but also other domains or profiles such as laboratory, patient care devices and personal health records received interest. Based on the results, factors influencing the adoption of external profiles or implementation guides of standards for local or national projects are discussed.